Effectiveness of Diabetes Self-Management Education in Developing Countries: A Systematic Review - Sukartini, Tintin; Pradipta, Rifky Octavia; Setyorini, Dwi Yoga; Fadilah, Superzeki Zaidatul; Susanti, Ika Adelia (International Journal of Psychosocial Rehabilitation, 2020)
Diabetes self-management education (DSME) helps patients with diabetes to process their capability to manage self-care. Coping skills and changing to a better behavior are the focus on the outcome. This review aimed to determine the effectiveness of DSME in type 2 diabetes mellitus patients (T2DM) living in developing countries. The Science direct, EBSCO, Proquest, and Scopus databases were searched. Randomized controlled trials from 2010 to 2020 were evaluated that focused on the effect of DSME for T2DM in developing countries. Detailed information from studies was summarized and included population, sample size, follow-up duration, DSME program conducted, outcomes and conclusion. The effectiveness of DSME on patients' condition was measured by calculating the improvement of the outcomes which compared the intervention and the control groups. The clinical outcome from DSME implementation was assessed by calculating the mean on the outright effect of the effect. Thirteen studies were included in this review. The characteristics of DSME implemented in the patient were varied depending on the patient and demographic background. Clinical outcomes (fasting, non-fasting blood sugar and hemoglobin) improved as they followed the therapy. The expected outcome from DSME affects the quality of life, knowledge, self- management behavior, adherence to medication, and self-efficacy. Some clinical conditions such as fasting, non-fasting blood sugar and hemoglobin improved after implementation of the DSME program. Complications from diabetes can be prevented by this simple and inexpensive intervention.